Quality of life in Patients with Melasma: A Hospital-Based Study - Mainali, Priyanka; Jha, Anil Kumar; Shrestha, Shristi; Thapa, Deeptara Pathak; Joshi, Smita; Amatya, Bibush (Nepal Journal of Dermatology, Venereology & Leprology, 2022)
Introduction: Melasma is the most common cause of facial melanosis and one of the most common diseases presenting to the Dermatology department. It can lead to psychological and emotional distress for the patients and can hamper their quality of life. So, this study was done to assess the quality of life among patients with melasma so that the need for couseling of these patients could be assessed along with medical treatment. Materials and Methods: This was a hospital based cross sectional study with 205 clinically diagnosed cases of melasma during the study period of one year. Melasma area severity index (MASI) score was recorded for each patient. Melasma quality of life was evaluated using the Melasma related Quality of Life (MELASQOL) score. MASI score and MELASQOL score were correlated using the Chi square test and socio-demographic details were also recorded. Results: The mean MASI score in our study was 14.39 and the mean MELASQOL score was 34.98. The correlation of the MASI score with the MELASQOL score was found to be statistically significant (p value = 0.000). Conclusion: MELASQOL score can be used to assess the quality of life in patients with melasma and the impairment in quality of life depends upon the MASI score.